HUBUNGAN HIGIENE DAN SANITASI PEDAGANG DENGAN KONTAMINASI SALMONELLA PADA DAGING AYAM POTONG DI PASAR TRADISIONAL PEKANBARU - Adhistie Indah Sari; Aras Mulyadi; Dedi Afandi (Program Pascasarjana Universitas Riau, 2015)
ABSTACTTerms of carcass and chicken meat quality is clarifying that Salmonella is a dangerous pathogen bacteria that responsible to cause gastroenteritis. With the result that, in food products are not allowed to contain Salmonella. Both hygiene and sanitation traders are very influence on food safety, so foods is matterials are not contaminated with bacteria. This research aims to determine the correlation between hygiene and sanitation traders with Salmonella contamination at chicken meats in traditional market of Pekanbaru. This research used analytic survey with cross sectional design. Research carried out in traditional markets in Pekanbaru and laboratory testing for microscopic investigation. The population was traders in traditional markets of Pekanbaru. The sampling technique is purposive sampling that consist of 10 samples that are 2 markets in Panam, 2 markets in Arengka, 2 markets in Labuh Baru, 2 markets in Cik Puan, and 2 markets in Kodim. The result of this research shown that there were 3 traders unhygiene products, where there were three samples of chicken meats contaminated with possitive Salmonella bacteria. While, there were four traders had poor sanitation. So, there were three samples of chicken meats with possitive Salmonella bacteria and one negative contaminated with Salmonella. Based on investigation of Lambda correlation, there is a correlation between hygiene traders with Salmonella contamination of chicken meats in traditional markets of Pekanbaru with p value 0,038 (p<0,05), and there is correlation between sanitation traders with Salmonella contamination of chicken meats in traditional markets of Pekanbaru with p value 0,038 (p<0,05).